Stiff Coatings on Compliant Biofibers: The Cuticle of Mytilus californianus Byssal Threads, - Holten-Andersen, Niels (2009)
For lasting holdfast attachment, the mussel Mytilus californianus coats its byssal threads with a protective cuticle 2-5 μm thick that is 4-6 times stiffer than the underlying collagen fibers. Although cuticle hardness (0.1 GPa) and stiffness (2 GPa) resemble those observed in related mussels, a more effective dispersion of microdamage enables M. californianus byssal threads to sustain strains to almost 120% before cuticle rupture occurs. Underlying factors for the superior damage tolerance of the byssal cuticle were explored in its microarchitecture and in the cuticular protein, mcfp-1. Cuticle microstructure was distinctly granular, with granule diameters (∼200 nm) only a quarter of those in M. galloprovincialis cuticle, for example. Compared with homologous proteins in related mussel species, mcfp-1 from M. californianus had a similar mass (∼92 kDa) and number of tandemly repeated decapeptides, and contained the same post-translational modifications, namely, trans-4-hydroxyproline, trans-2,3-cis-3,4-dihydroxyproline, and 3,4-dihydroxyphenylalanine (Dopa). The prominence of isoleucine in mcfp-1, however, distinguished it from homologues in other species. The complete protein sequence deduced from cDNAs for two related variants revealed a highly conserved consensus decapeptide PKISYPPTYK that is repeated 64 times and differs slightly from the consensus peptide (AKPSYPPTYK) of both M. galloprovincialis and M. edulis proteins.